BUBUR SURAN, KULINER TRADISIONAL SURAKARTA: ANTARA TRADISI DAN GAYA HIDUP - Kartika, Irma Ayu; Purnasari, Nurwulan (IJTIMAIYA: Journal of Social Science and Teaching, 2020)
Bubur Suran is one of the culinary festivals that routinely carried out in the Mangkunegaran Palace of Surakarta has not been studied yet. This study aims to explore the history and philosophy of Bubur Suran and study of nutritional aspects related to the lifestyle of the Javanese community in the Surakarta. The method used is a literature review and direct interviews with courtiers in Mangkunegaran. The results showed that Bubur Suran is one of the traditional culinary heritages that has a great historical value and can be a lifestyle identifier for the Surakarta settlement community in terms of nutritional aspects. During the modernization that has entered and developed in Indonesia, Mangkunegaran could maintain its tradition through Bubur Suran and make it a lifestyle until now. The Mangkunegaran using the culinary tradition of Bubur Suran to shows their identity and lifestyle to their social environment. Its showed that tradition could carry out a lifestyle without leaving the traditions which have been running from generation to generation.